http://ezaccess.library.uitm.edu.my/login?url=Strategic Orientation and Alliance Portfolio Configuration The Interdependence of Strategy and Alliance Portfolio Management - Wratschko, Katharina. (Gabler, 2009)
Strategic alliances have become an integral part of a firms strategy. Despite the growing empirical evidence of the strategic importance of alliances, the influence of a firms strategy on the design of its alliance portfolio has hardly been addressed by strategic management research. Following the resource-based view, social network theory and transaction cost theory, Katharina Wratschko shows the complex relationship between a firms business strategy and its alliance portfolio. Using Miles and Snows strategic typology as integrative framework, sample firms are clustered into strategic types. Results confirm that alliance portfolio characteristics (size, diversity, tie strength) differ significantly between strategy groups within the same industry. Hypotheses are tested with extensive data on the alliance portfolios of 90 US-listed pharmaceutical companies (roughly 2800 alliances). Results confirm the high interdependence of business strategy and alliance portfolio management.